Education in the Porfirio Diaz´z army of (1900 - 1910) (Tzintzun, Revista de Estudios Históricos, 2016)
During the regime of Porfirio Diaz, the army was well known for beingused as a repressive resource of the government. However, several investigations show the opposite conclusions, even though sometimes indeed,the army was used to quell riots of some importance, most of the times itwas reserved for other tasks. In addition its preparation, moral and disci-pline was very much affected due to the policy of “leeway” of the regime,as well as customs inherited from as far back as the colonial and indepen-dence. However, some efforts were made concerning improving educa-tion of the army. However, the reality was that these efforts gave veryfew and poor results, as priority was given to upper-class soldiers fromthe institution and the rest were relegated, with the consequent result:lower class soldiers were known by their ignorance and discontent, baseof any armed force. So, this little work is to show the conditions of edu-cation in one of the most important institution in the country: the army.
Keywords: Porfirio Diaz; military; education; social class; tropp